Validation of An Elbow Position Super-Twisting Sliding-Mode Controller for Upper-Limb Exosuit Using A Soft Position Sensor. Issue 1 (February 2021) - Pont-Esteban, D; Contreras-González, A F; Samper-Escudero, J L; Sáez-Sáez, F J; Ferre, M; Sánchez-Urán, M á
Abstract: Flexible exoskeletons, also known as exosuits, are robotic wearable devices intended to help healthy and unhealthy subjects in different tasks, such as daily life activities, load lifting or rehabilitation. A position control is required to assure stability and compliance in all assisted movements. In this paper, the authors propose the use of a flexible position sensor based on differential capacitance measurement as position feedback for the elbow joint in the flexible exoskeleton LUXBIT. This exosuit is controlled in position by a super-twisting sliding mode controller (SMC), which is robust against disturbances. Different movements involved in rehabilitation therapies are performed over three healthy subjects in order to evaluate the exosuit performance using this motion sensor. The measures given by the flexible sensor are compared to the ones obtained by OptiTrack motion capture system, which are used as ground truth.